How do we know they're getting better? : assessment for 21st-century minds, K-8 - Barell, John. (Thousand Oaks, Calif. : Corwin, 2012)
How do we measure students' inquiry, problem-solving, and critical thinking abilities so that we know they are prepared to meet the challenges of the 21st century? John Barell explains how inquiry leads to problem solving and provides specific steps for formative assessment that informs instruction of 21st century skills. Included are examples that show how to use today's technology in the classroom and how to use inquiry to develop and assess students' ability to.
Think critically and creatively.
Adapt and become resourceful.
Develop a sense of leadership, responsibility, and global awareness.
The author challenges teachers to reflect on their own learning, thinking, and problem-solving processes as well as those of their students. The text provides frameworks for monitoring students' progress and guidelines for communicating with parents. Teachers will find examples from all grade levels that illustrate how to observe and assess students' growth in their development of 21st century capacities, making this a timely and valuable resource.
An overview -- Teacher modeling: "out of our comfort zones!" -- Designing the invitation-to-risk environment -- Curriculum for the 21st century -- Conducting pre-assessments: sitting by the judge -- Formative assessments: gathering a "wealth of information" -- From statements to good questions in kindergarten -- "My inquiry skills shot through the roof!": grade 6 -- How "STEM" changed my life!" -- From cookie cutter a to self-directed student -- Inquiry begins at home -- After action reviews: how to build upon what we know.
Includes bibliographical references and index.
Keywords: Educational tests and measurements -- United States; Education, Elementary -- United States -- Evaluation; Middle school education -- United States -- Evaluation; Curriculum change -- United States; Education -- Aims and objectives -- United States